Influence of Demographic Factors on Women’s Career Development in Nepalese Commercial Banks - Shrestha, Indira (Journal of Nepalese Business Studies, 2024)
In the business world, women's employment careers have been a significant problem. It has been determined that a variety of factors influence women's career outcomes in organizational contexts. Thus, the study's goal was to examine how demographic variables affected Nepalese women's career advancement in commercial banks. The study's population was female employees in commercial banks who held supervisory positions or above. Samples of 319 women were collected for the research. A purposeful sampling technique was employed to get the respondents' responses. To analyze the influence of demographic characteristics on career development, descriptive as well as analytical research designs were utilized. Among the statistical methods used were the one-way ANOVA, independent t-test, mean, and percentage frequency. The results showed that factors influencing women's careers include age, income, and service year in addition to marital status, and designation. However, education did not affect women’s careers. The study's conclusions offer insightful information on the potential influence of demographic variables on the careers of females. The study's conclusions will be valuable to the existing literatures related to how demographic elements affects carrers of women. Additionally, supports organizations in focusing on creating rules that suit their unique set of circumstances.